The image of Russia in the Eastern Christian and Ottoman Muslim eschatology of modern times - Taras Kobishchanov (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология, 2024)
The reason for the study was the appearance in the Lebanese chronicle of the late XVIII century of the mysterious figure of “King Michael of Muscovy”. In search of a solution, it turned out to be necessary to consider the evolution of the image of the “yellow people”: Banu al-Asfar. The article explores how, having appeared in Ancient Judea, this nickname was transferred by the Jews, followed by the Arabs to the Romans and other Europeans. Further ways of transforming this term and filling it with new meanings in the Christian and Islamic prophetic traditions are analyzed. It shows how, under the influence of the Old Testament and the hadiths of the Sunnah, the image of the “yellow people” penetrated into the Byzantine apocalypse and, having developed inside it, spread throughout the Christian world and got back into the Ottoman-Muslim eschatology. The role of myths about “yellow people” and “blond-haired people” in the system of self-identification and interpretation of images of “friend and foe” among Christian and Muslim subjects of the Ottoman Empire is demonstrated, the significance of expectations of the invasion of the "blond race" during the Russian-Turkish wars of the last third of the XVIII century is shown. As a result, the meaning of the figure of “Moscow King Mikhail” as the tsar-liberator from the Old Testament and medieval prophecies is revealed.